Association of Alzheimer’s and Lewy body disease pathology with basal forebrain volume and cognitive impairment - Julia Schumacher; Stefan Teipel; Alexander Storch (Alzheimer’s Research & Therapy)
Abstract Background Degeneration of the basal forebrain cholinergic system is a hallmark feature shared by Alzheimer’s disease (AD) and Lewy body disease (LBD) whereas hippocampus atrophy is more specifically related to AD. We aimed to investigate the relationship between basal forebrain and hippocampus atrophy, cognitive decline, and neuropathology in a large autopsy sample. Methods Data were obtained from the National Alzheimer’s Coordinating Center (NACC). Basal forebrain and hippocampus volumes were extracted using an established automated MRI volumetry approach. Associations of regional volumes with pathological markers (Braak stage, CERAD score, and McKeith criteria for LB pathology) and cognitive performance were assessed using Bayesian statistical methods. Results We included people with autopsy-confirmed pure AD (N = 248), pure LBD (N = 22), and mixed AD/LBD (N = 185). Posterior basal forebrain atrophy was most severe in mixed AD/LB pathology compared to pure AD (Bayes factor against the null hypothesis BF10 = 16.2) or pure LBD (BF10 = 4.5). In contrast, hippocampal atrophy was primarily associated with AD pathology, independent of LB pathology (pure AD vs. pure LBD: BF10 = 166, pure AD vs. mixed AD/LBD: BF10 = 0.11, pure LBD vs. mixed AD/LBD: BF10 = 350). Cognitive performance was more impaired in AD pathology groups, with Braak stage being the strongest predictor. Hippocampal volume partially mediated this relationship between tau pathology and cognitive impairment, while basal forebrain volume had a limited role in mediating the relationship between pathological burden and cognitive outcomes. Conclusion In a heterogeneous autopsy sample, AD and LB pathology both contribute to cholinergic basal forebrain degeneration whereas hippocampus atrophy is more specifically related to AD pathology. Cognitive deficits are primarily associated with tau pathology which is partly mediated by hippocampus, but not basal forebrain atrophy.